Intervention in new amateur subtitling cultures: a multimodal account - Pérez-González, Luis (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Recent developments in the audiovisual marketplace have led to an increasing compartmentalization of subtitling audiences and the emergence of amateur subtitling cultures that aim to cater for the idiosyncratic demands of their target audience niche. Fansubbing, i. e. the subtitling of Japanese animated films by fans, is one of the most influential and successful of such amateur cultures. This article examines the genealogy of this peculiar phenomenon, describes some of its most distinctive subtitling practices and explores the effects of its interventionist agenda. Drawing on the apparatus of multimodal theory and the insights provided by a small purpose-built corpus, this paper argues that fansubbing exploits traditional meaningmaking codes in a creative manner and, more importantly, criss-crosses the traditional boundaries between linguistic and visual semiotics in innovative ways.